2017
DOI: 10.1186/s12882-017-0588-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of peritoneal dialysis-related peritonitis on mortality in peritoneal dialysis patients

Abstract: BackgroundResults concerning the association between peritoneal dialysis-related peritonitis and mortality in peritoneal dialysis patients are inconclusive, with one potential reason being that the time-dependent effect of peritonitis has rarely been considered in previous studies. This study aimed to evaluate whether peritonitis has a negative impact on mortality in a large cohort of peritoneal dialysis patients. We also assessed the changing impact of peritonitis on patient mortality with respect to duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
83
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 37 publications
(42 reference statements)
16
83
0
1
Order By: Relevance
“…Maybe we can explain this with a longer follow-up period than others. Comparing with the other study patients our rate of transferred to haemodialysis (30.9% vs 8.4%-29.4%) and renal transplantation (9% vs. 1.6%-39%) were similar [10,18,19,23].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Maybe we can explain this with a longer follow-up period than others. Comparing with the other study patients our rate of transferred to haemodialysis (30.9% vs 8.4%-29.4%) and renal transplantation (9% vs. 1.6%-39%) were similar [10,18,19,23].…”
Section: Discussionsupporting
confidence: 53%
“…Although rates varied from our results, the same reasons were reported in the other studies. In some studies, cardiovascular diseases were shown to be the most common cause of death (39%-60%), infectious causes were the second most common cause of death (17.6%-40%) among PD patients [8,9,14,17,19,23,24]. The rate of PD survivors was reported to be 58.9% in a 6-year study from Japan [18] and %46.3 in a 2-year study from China [23].…”
Section: Discussionmentioning
confidence: 99%
“…Peritonitis episodes could cause membrane permeability changes and ultrafiltration declines with time on PD, which finally leads to technique failure. Peritonitis is widely recognized in the literature as affecting PD patients' 'technique survival and mortality' [14][15][16]. In our study, it is only by using a competing risk model that we found previous history of a peritonitis episode as a predictive factor of transfer to HD.…”
Section: Discussionmentioning
confidence: 60%
“…In china, the number of ESRD patients receiving PD therapy is rapidly growing in recent years [37]. Patients on long-term dialysis have a significantly increased risk of mortality, and cardiovascular disease (CVD) and infection are most common causes of death in dialysis patients [38,39] have shown a variety of risk factors that predict the outcomes of dialysis patients, including age [40], sex [41], RRF [42], blood pressure [43,44], comorbidity [45], BMI [46][47][48][49], serum ALB [50,51], pre-ALB [52][53][54], TC [55][56][57][58], TG [59,60], VLDL [61], HB [62], Ca, P [63], PTH, ALP [64], UA [65,66], K, CRP [67], dialysis adequacy [68,69], incident peritonitis [70,71] and so on. Much effort has been done to maintain stable blood pressure, correct anemia and electrolyte disturbance as well as ensure dialysis adequacy and prevent peritonitis, in order to improve the long-term outcomes of dialysis patients.…”
Section: Discussionmentioning
confidence: 99%